The Impact Analysis of Service Quality and Facilities on Patient Loyalty (Study at the Kidney and Hypertension Clinic - BMS Jrakah, Semarang City) - AMALIA NURHIDAYAH, EVINTA; Heni Subekti,; Evinta Amalia Nurhidayah, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract Lestari Kidney and Hypertension Clinic - BMS Jrakah is the second specialized clinic for treating kidney complaints (dialysis) in Semarang after KGHL. The need for fast, professional services of course with complete equipment related to kidney problems, especially requiring dialysis, cannot be denied that it needs to be improved. The facilities provided will have an impact on patient satisfaction so that patients will trust and be confident in undergoing treatment at the Kidney and Hypertension Clinic – BMS Jrakah. Using population and sample methods in this study to determine the sampling technique using non-probability sampling, namely purposive sampling. The value of the t-test results is positive and the sig value is smaller than the specified significance level. This means that the quality of service can affect the level of loyalty. The higher the quality of service provided by the Lestari Kidney and Hypertension Clinic - BMS Jrakah in Semarang City, the loyalty of patients of the Lestari Kidney and Hypertension Clinic - BMS Jrakah in Semarang City will increase. Service quality partially has a positive and significant effect on patient loyalty, which can be seen from the t test results, namely t count (5.472) > t table (2.02809), with a significance of 0.000 < 0.05. It can be concluded that the better the service provided will increase patient loyalty at the Lestari Kidney and Hypertension Clinic - BMS Jrakah in Semarang City. Keywords: Service quality, Facilities, Patient loyalty